Aplikasi Daftar Cek Masalah (DCM) Bagi Anak Usia Dini di Wilayah Lahan Rawa - Akhmad Rizkhi Ridhani; Aminah Aminah; Zainal Fauzi (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2020)
Guidance and counseling teachers must innovate and continue to upgrade themselves in relation to the provision of therapeutic services, considering the problems that occur in society today are very complex and require effective and efficient services. Therefore, it is necessary to develop a DCM (Problem Checklist) instrument application to make it easier for practitioners engaged in therapeutic services to sort out complex problems for counselees or students. The research method used in this research is research and development methodology by adopting the brog and gall stages which are simplified into 5 stages, namely: (1) preliminary study. (2) hypothetical development, (3) hypothetical model review, (5) hypothetical model revision. The research instrument used by the researcher is using a wide expert validation which includes 2 types of validators, namely: (1) expert validators in the field of guidance and counseling, and (2) practitioner validators to test products developed by researchers. The data analysis used in this research is qualitative analysis. The results of this study based on a qualitative validation test showed that this model was generally considered good. However, there are some improvements in the model developed by researchers based on input from experts, both academics and practitioners so that the model is really effective and efficient for use in the field. It is recommended to the next researcher to conduct a limited trial using this model.